Evaluating cassava peel-based substrates on the yield and nutritional quality of oyster mushroom (Pleurotus ostreatus) - Olaniyan, S.A.; Hussein, J.B.; Oke, M.O.; Akinwande, B.A.; Workneh, T.S.; Maziya-Dixon, B.; Adeyemi, I.A. (2025)
The study explores the impact of composting cassava peel-based substrates on the yield and nutritional quality of oyster mushrooms in a soilless culture system, as environmental pressures from agricultural waste disposal prompt the implementation of sustainable solutions. Cassava peels, rice bran, and sawdust waste were collected, washed, air-dried, and shredded. The substrates were inoculated with P. ostreatus spawn and placed in a growing room for 5–7 weeks. The yield performance, proximate composition, antinutrients, and mineral content of oyster mushrooms were evaluated using standard procedures. The yield results ranged from 113.20 g (22.64% biological efficiency) to 341.40 g (68.28% biological efficiency). The proximate composition ranged between 88.05–90.25%, 1.80–3.75%, 0.45–0.85%, 2.55–4.85%, 1.55–2.30%, and 2.05–4.10%, respectively, for moisture contents, protein contents, crude fats, ash, crude fibres, and carbohydrates. The antinutrients ranged between 10.40–12.43 mg/100 g, 6.00–7.17 mg/100 g, 13.63–16.07 mg/100 g, 7.73–9.10 mg/100 g, and 0.37–0.70 mg/100 g, respectively, for oxalate, tannin, saponin, phytate, and cyanogenic glycosides. The mineral ranged between 92.67–97.67 mg/100 g, 3.37–3.77 mg/100 g, 2.50–2.93 mg/100 g, 31.67–38.00 mg/100 g, and 101.67–109.33 mg/100 g, respectively, for calcium, iron, magnesium, potassium, and phosphorus contents. The increase in yield and nutritional quality, while maintaining antinutritional components below acceptable consumption limits, suggests that cassava peels could be employed as a substrate for mushroom cultivation. This study promotes a circular economy by reusing agricultural waste for high-value food production and bioprocessing, promoting sustainable use of byproducts while reducing environmental impact.